Mental disorders among college students in the World Health Organization World Mental Health Surveys. Issue 14 (3rd August 2016) - Auerbach, R. P.; Alonso, J.; Axinn, W. G.; Cuijpers, P.; Ebert, D. D.; Green, J. G.; Hwang, I.; Kessler, R. C.; Liu, H.; Mortier, P.; Nock, M. K.; Pinder-Amaker, S.; et al.
Abstract : Background: Although mental disorders are significant predictors of educational attainment throughout the entire educational career, most research on mental disorders among students has focused on the primary and secondary school years. Method: The World Health Organization World Mental Health Surveys were used to examine the associations of mental disorders with college entry and attrition by comparing college students ( n = 1572) and non-students in the same age range (18–22 years; n = 4178), including non-students who recently left college without graduating ( n = 702) based on surveys in 21 countries (four low/lower-middle income, five upper-middle-income, one lower-middle or upper-middle at the times of two different surveys, and 11 high income). Lifetime and 12-month prevalence and age-of-onset of DSM-IV anxiety, mood, behavioral and substance disorders were assessed with the Composite International Diagnostic Interview (CIDI). Results: One-fifth (20.3%) of college students had 12-month DSM-IV/CIDI disorders; 83.1% of these cases had pre-matriculation onsets. Disorders with pre-matriculation onsets were more important than those with post-matriculation onsets in predicting subsequent college attrition, with substance disorders and, among women, major depression the most important such disorders. Only 16.4% of students with 12-month disorders received any 12-month healthcare treatment for their mental disorders. Conclusions: Mental disorders are common among college students, have onsets that mostly occur prior to college entry, in the case of pre-matriculation disorders are associated with college attrition, and are typically untreated. Detection and effective treatment of these disorders early in the college career might reduce attrition and improve educational and psychosocial functioning.